AWARENESS OF THE POPULATION IN RURAL REGIONS OF SERBIA ABOUT RENEWABLE ENERGY SOURCES - Žikić , Srđan; Trifunović, Dragana; Lalić, Goran; Jovanović, Mihailo (Economics of Agriculture, 2022)
Public awareness about renewable sources can contribute to social acceptance of sustainable development projects. The purpose of this study was to determine attitudes and level of awareness of the population of rural regions of Serbia about renewable energy sources. The research method included the random sampling of 400+ respondents in Southern, Eastern and Central Serbia. A questionnaire with closed-ended questions for expressing attitudes (Likert scale) was used. Collected data have been analyzed with SPSS. The results of this study clearly show that the citizens of rural regions of Serbia are relatively poorly informed not only of general aspects of energy production and consumption, but of specific aspects related to the use of renewable energy sources. This investigation emphasizes the need for intensive public information campaign about the advantages and benefits of renewable energy in order to have broader public support for the implementation of this form of energy into energy sector of Serbia.